Benthonic assembly and its correlation with the geodiversity of the east continental shelf of Ceará (Brazilian equatorial margin) - Nkouamen Nemzoue, Peguy Noel; Maia de Almeida, Narelle; Satander Sá Freire, George; Tchouankoue, Jean Pierre; Noucoucouk, Arrissa Agathe; de Mendeiros Lima, Rafael (Quaternary and Environmental Geosciences, 2024)
Bioclastic sediments have economic value due to their high concentration of calcium minerals and can be used as soil amendments in agriculture, in cement factories, for animal feed formulation, and in the cosmetic industry. In Brazil, they are widely exploited on the continental shelf. Although the sedimentary facies of the Ceará continental shelf are known, there is no information about the composition of bioclastic constituents, their diversity, and distribution. This study aims to identify the constituents of marine benthic communities and their relationship with abiotic factors such as depth, morphology, and sedimentary facies. To this end, analyses of remote sensing data, bathymetry, and sediment samples were conducted. Features such as submerged dunes (oblique, parallel, and transverse), beach sandstones, and paleochannels were observed, and, according to physiographic and morphological aspects, five zones were interpreted (1. suspended sediment zone, 2. transverse dune zone, 3. oblique dune zone, 4. reef construction zone, and 5. flatbed zone). Sedimentological analyses identified components with their respective relative frequencies: bryozoans (35.5%), calcareous algae (27%), foraminifera (12.3%), molluscs (12%), cnidarians (4%), echinoderms (3.9%), sponges (3.5%), and arthropods (1.7%). Principal component analyses (PCA) showed a positive correlation between the biotic components (calcareous algae, sponges, and cnidarians) and the abiotic factors (depth 20-40 m, zones 2 and 4 (Z2 and Z4), and the bioclastic gravelly sand facies (BGS)). Otherwise, arthropods tend to occur from 40 to 60 m depth and are commonly associated with the biolithoclastic sand facies (BLS), while echinoderms and molluscs tend to occur in shallower regions (0-20 m), associated with zone 1 (Z1) and to the bioclastic gravel (BG) and bioclastic sand with gravel (BSG). This research demonstrates the relationship between geology, geomorphology, and benthic marine life in the region and provides a valuable database for measuring and monitoring the area, which has attracted attention from various sectors of the Blue Economy, especially during the Decade of the Oceans.